LASER RAMAN SPECTROSCOPIC INVESTIGATIONS OF SOME FLUOROXENON COMPOUNDS - Landa, Benjamin (My University, 1974)
The Raman spectra of a number of salts of fluoro- and oxy-fluoro cations of xenon compounds, in a variety of oxidation states are reported. The preparation of some of these compounds is reported for the first time. Characteristic frequencies along with comprehensive assignments are given for the Xe₂F₃⁺, XeF⁺, XeF₃, XeOF₃⁺, Xe₂OF⁺, XeF₅⁺ and Xe₂F₁₁⁺ cations, and some other related compounds both in the solid state and in HF solution. Reactions of XeF₂ with BF₃ have been shown to give the new BF₄⁻ salts, XeF⁺BF₄⁻ and Xe₂F₃⁺BF₄⁻, while the reaction of XeF₄ with AsF₅ has been shown to give the new salt XeF₃⁺As₂F₁₁⁻⁻. Largely, by the aid of Raman spectroscopy, the molecular geometries of these cations are shown to be in accord with electron pair repulsion theory.
Direct spectroscopic evidence is presented for the first time for the presence of weak covalent interaction, i.e., fluorine bridges, in a number of the salts studied. With the aid of the available X-ray crystallographic data, and the vibrational data presented, it was found that fluorine bridge interactions increase in strength in the series XeF₅⁺ < XeF₃⁺ < XeF⁺. Thus, in contrast to the previously supposed order the fluoride ion donating ability of the fluorides was found to decrease, in the order XeF₆ > XeF₄ > XeF₂.
A useful correlation has been found between the xenon-fluorine stretching frequencies and the bond lengths. This correlation has been found to hold for a wide variety of fluorocations, and neutral molecules, in a number of different oxidation states and for a wide range of Xe-F bond lengths, including the Xe---F bridge bonds.
Keywords: Chemistry; Chemistry